PROSES PEMBELAJARAN BIOLOGI PADA MATERI SISTEM PEREDARAN DARAH MANUSIA DI KELAS VIII SMP NEGERI 3 RAMBATAN - NAJMIATUL FAJAR (Ta'dib, 2016)
Leaning process can influence students’ achievement. The lack of students’ understanding on the particular materials could decrease students’ achievement. The purpose of this research is to evaluate the leaning process of biology in human circulator system at the eight grade of Junior High School (SMP) 3 Rambatan covering the lesson plan, implementation of learning proces, evaluation, and students’ learning outcome. This researh was descriptive using qualitative approach. It was conducted at SMP 3 Rambatan. Data were collected using IPKG on lesson, interview, document, and field notes. The reseach shows as follows: (1)  the format of lesson plan used by the teachers has fulfilled the IPKG and could be categorized into good; (2) the learning process had not yet referred to the IPKG but could be classified as good and enough category; (3) the evaluation of learning process had not referred to IPKG; (4) students’ learning activities were still low; and (5) students’ learning outcome were unsatisfactory.Kata Kunci: proses pembelajaran biologi, sistem peredaran darah manusia, aktivitas   siswa, hasil belajar.